Názory budoucích pedagogů na začlenění dětí s postižením do tělesné výchovy v Jihoafrické republice Attitudes of future physical educators toward teaching children with disabilities in physical education in the Republic of South Africa - Liz Bressan; Martin Kudláček; Radka Bartoňová (Palacky University, 2007)
Jednou z bariér, týkající se začlenění dětí s postižením do tělesné výchovy, mohou být negativní postoje učitelů. Tyto postoje mohou pramenit z neznalosti nebo nedostatku zkušeností s dětmi s postižením. Pro překonání těchto bariér je nezbytné změnit postoje těch, kteří mají být prostředníky v inkluzi. Tripp a Sherrill (1991) opakovaně vyzdvihují význam postojů v aplikovaných pohybových aktivitách a jejich výzkumu. Teoreticky podložený výzkum o utváření postojů může stanovit rámec porozumění faktorům, které působí na vztah mezi postojem a chováním (Tripp & Sherrill, 1991). V rámci výzkumu postojů jsme upravili dotazník "Attitude Toward Teaching Individuals with Physical Disabilities in Physical Education" (ATIPDPE) pro studenty oboru "sport science" na Universitě Stellenbosch v Jihoafrické republice. Do výzkumu bylo začleněno 60 studentů. Utvořili jsme dvě skupiny, ve kterých bylo 30 studentů se specializací trenérství osob se zdravotním postižením a 30 studentů bez této specializace. Porovnali jsme skupiny v komponentech teorie plánovaného jednání a výsledky ukázaly, že mezi postoji studentů v těchto dvou skupinách není statisticky významný rozdíl. The Republic of South Africa has undergone significant changes with regard to people with disabilities in the past number of years, which have also included changes in legislation and education. In the education of children with disabilities, inclusion is quite a new phenomenon. In order to prepare for inclusion, universities must focus on teacher preparation. Sherrill (1998) emphasised the role of attitudes in teacher preparation and therefore we have focused on the attitudes of university students toward inclusion. The aim of this study was to examine the differences in attitudes between two groups of students of the Department of Sport Science at the University of Stellenbosch in the Republic of South Africa. 30 of the students were specialized in coaching people with disabilities and 30 students were without this specialization. The adapted version of the questionnaire "Attitudes Toward Teaching Individuals with Physical Disabilities in Physical Education" (ATIPDPE), an instrument designed according to TPB (Ajzen, 1991, 2000) was used. To compare the attitudes of the two groups of students from the Republic of South Africa, a one way analysis of variance (ANOVA) was used. The computer program SPSS PC 11.0 was used to determine significant differences between students in intention to include participant with physical disability into general activity and behavioral belief. Two groups were compared with regard to TPB components and the results showed no significant differences between these groups.